CNS delivery of anti-CD52 antibodies modestly reduces disease severity in an animal model for multiple sclerosis - Jeroen FJ Bogie; Elien Grajchen; Elien Wouters; Bieke Broux; Piet Stinissen; Bart Van Wijmeersch; Jerome JA Hendriks (SAGE Publishing, 2020)
Background and aims: Alemtuzumab is a humanized monoclonal antibody that depletes CD52-bearing B and T lymphocytes. Clinical trials defined that systemic administration of alemtuzumab reduces disease severity in the relapsing-remitting phase of multiple sclerosis (MS). However, its efficacy in progressive MS patients is limited, which may reflect the inability of alemtuzumab to cross the reconstituted BBB in these patients. Objective: to study whether central nervous system (CNS) delivery of anti-CD52 antibodies reduces disease severity and the neuroinflammatory burden in the experimental autoimmune encephalomyelitis (EAE) model. Methods: Anti-CD52 antibodies were administered intrathecally during the acute and chronic phases of EAE. Flow cytometry and immunohistochemistry were utilized to define immunological and pathological parameters. Results: We show that subcutaneously administrated anti-CD52 antibodies completely abolish EAE disease severity. CNS delivery of anti-CD52 antibodies during both the acute and chronic phases of EAE moderately reduces disease severity and the neuroinflammatory burden. Our findings further suggest that CNS delivery of anti-CD52 antibodies impacts both the peripheral and CNS immune cell compartments in the EAE model but not in healthy mice. Conclusion: Collectively, our findings highlight the therapeutic potential of CNS delivery of alemtuzumab for the treatment of progressive as well as early MS.